Fatal bacteremia due to immotile Vibrio cholerae serogroup O21 in Vientiane, Laos – a case report - Moore Catrin E; Lattana Olay; Vongsouvath Manivanh; Davong Viengmone; Arakawa Eiji; Nakatsu Masami; Phetsouvanh Rattanaphone; Nakamura Satoshi; Newton Paul N (Annals of Clinical Microbiology and Antimicrobials, 2008)
Abstract Background Human infections with non-O1, non-O139 V. cholerae have been described from Laos. Elsewhere, non cholera-toxin producing, non-O1, non-O139 V. cholerae have been described from blood cultures and ascitic fluid, although they are exceedingly rare isolates. Case presentation We describe a farmer who died with Vibrio cholerae O21 bacteremia and peritonitis in Vientiane, Laos, after eating partially cooked apple snails (Pomacea canaliculata) and mussels (Ligumia species). The cultured V. cholerae were non-motile. PCR detected ompW and toxR gene regions but not the ctxA, ompU, omp K and TCP gene regions. Although the organisms lacked flagellae on scanning electron microscopy, they possessed the Vibrio flagellin flaA gene. Conclusion Severe bacteremic non-O1, non-O139 V. cholerae is reported from Laos. The organisms were unusual in being non-motile. They possessed the Vibrio flagellin flaA gene. Further research to determine the reasons for the non-motility and virulence is required.